Displacement-Based Simplified Seismic Loss Assessment of Steel Buildings. Issue 1 (24th June 2020) - Cantisani, G.; Della Corte, G.; Sullivan, T.J.; Roldan, R.
ABSTRACT: Evaluating losses consequent to damages induced by earthquakes has become one main paradigm in seismic performance assessment. Within this context, this paper explores a simplified seismic loss assessment methodology for steel structures that utilises displacement-based assessment in place of non-linear dynamic analyses. To this end, two case studies have been considered: (i) an archetype existing single-storey non-residential building, (ii) a prototype new multi-story residential building. Comparing results obtained using the fully probabilistic and the simplified displacement-based assessment methodologies allows the benefits of the simplified method to be highlighted. Possible difficulties encountered in applying the simplified method are also identified.